KONSEP SISTEM PENGELOLAN ZAKAT DI INDONESIA PENGENTAS KEMISKINAN PENDEKATAN SEJARAH - Muhammad Ngasifudin (JESI (Jurnal Ekonomi Syariah Indonesia), 2015)
Abstract Zakat is the primary means of communication between man and another man in bermasyarat sake compose a harmonious and humane life . The role of Zakat , both property and tithes would be more visible subtle and implemented together with other instrumental value that is usury. Obligation of alms giving ﬁ rm and absolute top of every Muslim, premises object property that is property and income that have fulﬁ lled the obligation of zakat and charity penunian -value embodied wisdom and universal values that beneﬁ t the community life and poverty pengentas Keywords: Zakat, Equity, Poverty